2021
DOI: 10.1242/dmm.049103
|View full text |Cite
|
Sign up to set email alerts
|

Activation of innate immunity during development induces unresolved dysbiotic inflammatory gut and shortens lifespan

Abstract: An early-life inflammatory response is associated with risks of age-related pathologies. How transient immune signalling activity during animal development influences life-long fitness is not well understood. Using Drosophila as a model, we find that activation of innate immune pathway Immune deficiency (Imd) signalling in the developing larvae increases adult starvation resistance, decreases food intake and shortens organismal lifespan. Interestingly, lifespan is shortened by Imd activation in the larval gut … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Collectively, these results well accord with the previous reports of positive association of the pathways of ribosome and autophagy with longevity [52] and negative association of genome instability [53,54] and activated immune reaction [55,56] with lifespan. Among the alteration of the expression levels of the genes, the pathways of genome stability were most notable (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, these results well accord with the previous reports of positive association of the pathways of ribosome and autophagy with longevity [52] and negative association of genome instability [53,54] and activated immune reaction [55,56] with lifespan. Among the alteration of the expression levels of the genes, the pathways of genome stability were most notable (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, we did not see major differences between axenic and conventionally raised wild-type flies in this study. Previous studies have already revealed the role of Imd signalling in controlling microbiome load and diversity, preventing dysbiosis [46,88–90]. More recently, use of ΔAMP14 flies revealed a key role of AMPs to control bacteria in the gut, notably the Gram-negative bacterium Acetobacter , and accordingly, ΔAMP14 flies have increased microbiome load upon aging ([25] and Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this, we did not see major differences between germ-free and conventionally raised wild-type flies in this study. Previous studies have already revealed the role of Imd signalling in controlling microbiome load and diversity, preventing dysbiosis (Guo et al, 2014; Li et al, 2016; Liu et al, 2022; Yamashita et al, 2021). The specific microbiome of a given research group could also change the impact of germ-free conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Canton-S, w Dah , w CS (Canton-S backcrossed to w iso31 eight times), w iso31 , and yw flies were used as control strains. Other fly lines used in this study were Dredd B118 [26], 5966 GS , UAS-GFP [44], WBFB GS (S106+S32) [45], Uro GS [46], Su(H)GBE-LacZ, esg ts , NP1-Gal4 [47], UAS-caudal-RNAi (VDRC, v3361), UAS-Rel-RNAi (BDSC, 33661), PGRP-LC-RNAi (BDSC, 33383), and UAS-PGRP-LE-RNA i (BDSC, 60038). The Rel E20 , PGRP-LC E12 , and PGRP-LE 112 lines have been described previously [17,48].…”
Section: Methodsmentioning
confidence: 99%